Investigation of the Effect of Weft Yarn Parameters on the Elasticity and Recovery Properties of Stretch Denim Fabrics - Pelin Gürkan ünal; Dilara Konal (Journal of Natural Fibers, 2022)
The aim of this study was to examine the effect of weft yarn parameters on the elasticity and recovery properties of stretch denim fabrics. For this purpose, frequently used denim fabric was taken as a reference point, and to study the elasticity, and dimensional change properties of the reference fabric, the production of new denim fabrics was designed with the use of different core yarns in the weft direction with different ratios. As a result, five different denim fabrics containing three different weft yarns with different sequences in Twill 3/1 Z weave type were produced. All fabric samples were prepared as half legs form and rinse washing, stone washing and stone+bleaching washing processes were applied. Elasticity, residual extension, and dimensional stability tests of the samples were performed, and the results were analyzed regarding the weft yarn properties and finishing processes. In addition to these tests, mass per unit area was examined to observe the weight changes of the fabrics due to shrinkage after washing. All tests were evaluated statistically. According to the analysis, it was found that the fabric performance was affected by the weft yarn type, and the different washing processes.